Kalliovarat ja kallioperän tutkimus - Niini, Heikki (Vuoriteollisuus, 1982)
Summary: Bedrock resources and research.
Keywords: Suomi; Finland; taloudellinen geologia; kallioperä; mineraalivarat; rakennusaineet; maanalaiset tilat; katsaus; economic geology; bedrock; mineral resources; construction materials; underground installations; review